The Multinationalization of the Transport Sector - Mario Larch (Tinbergen Institute, 2005)
According to the World Investment Report 2004, the structure of Fmhas shifted towards services. Further, the composition of services FDI isalso changing from trade and finance to such industries as electricity, water ,telecommunications, storage and transportation. In the latter sector the valueof FDI stock rose 16-fold between 1990 and 2002. Incorporating a transportsector dominated by multinationals and economies of scale in a modelof thenew trade theory leads to different predictions regarding the volume of tradeand income as compared to a model with iceberg transport costs. It alsoopens up a further possibility for specialization.
Keywords: F12; F23; 330; Multinationals; Transport sector; Iceberg transport costs; Economies of Scale; Verkehrsgewerbe; Globalisierung; Multinationales Unternehmen; Skalenertrag